Implementasi Manajemen Mutu Terpadu dalam Sistem Manajemen Sarana Prasarana di Pondok Pesantren Ulumul Qur’an Wonosobo - Tafyiroh Tafyiroh; Subiyantoro Subiyantoro (JIEM (Journal of Islamic Education Management), 2023)
At Islamic boarding schools tend to have skin diseases that are contagious due to lack of personal hygiene. Personal hygiene is an effort that can be made to improve the health of students in the hope that infectious diseases will decrease. This study aims to analyze the implementation of integrated quality management in the infrastructure management system at the Ulumul Qur'an Islamic Boarding School, Wonsosobo. The approach used in this study is an exploratory qualitative approach. Data collection techniques using observation techniques, interviews and documentation. The informants in this study were the leaders of the pesantren, administrators and ustadz-ustdzah. The results of this study indicate that the Ulumul Qur'an Islamic Boarding School has optimized the management of infrastructure facilities in an effort to improve personal hygiene behavior for its students.